Forest product markets, forests and poverty reduction - Belcher, B. (2005)
There is a new and increasing emphasis on poverty alleviation and livelihoods improvement in forestry, representing both a challenge and an opportunity. This paper briefly reviews the evolution of the ‘livelihoods’ issue, analyzes the concept of ‘poverty alleviation’ and discusses means by which forestry can contribute to livelihoods improvement. It focuses on the contributions of forest products and markets, questioning the typical timber vs non-timber dichotomy. The role and the potential of a forest product is determined more by the socio-economic and environmental context of the production, processing and marketing system than by the physical characteristics of the product itself. This is important as new opportunities arise through increased control of resources by local people and new markets for forest products. Helping achieve poverty alleviation through forestry requires protecting poverty mitigation functions, enhancing income and employment options, and taking advantage of opportunities to build and strengthen local institutions through policies and project-level interventions.